The Politics of Risk in the Digital Services Act - Rachel Griffin (Weizenbaum Journal of the Digital Society)
The EU’s 2022 Digital Services Act requires large online platforms to regularly assess and mitigate ‘systemic risks’ to various public-interest goals, including fundamental rights, civic discourse, public health and security. Drawing on social constructionist understandings of risk, this article theorizes systemic risk management under the DSA as an arena for political power and contestation, since translating its broadly-defined abstract principles into actionable risk management procedures will entail making many contestable political decisions about how online platforms should be governed. This raises the question: who will exercise power in these decision-making processes? Providing some first answers to this question, this article makes three key contributions. First, it maps the key stakeholder groups involved, and the legal and institutional mechanisms through which they can participate in DSA systemic risk management. Second, it critically analyzes the power dynamics and unequal resources that will structure stakeholder participation. Third, this stakeholder mapping provides a foundation for future research on the politics of DSA systemic risks. The article concludes with reflections on directions for future research on the political agendas, priorities and strategies that shape platform governance.